Myanmar Economic Monitor, December 2020 : Coping with COVID-19 - World Bank (World Bank, Washington, DC, 2020)
The second wave of the Coronavirus (COVID-19) pandemic has amplified Myanmar’s public health and economic challenges. Domestic cases of Coronavirus (COVID-19) have risen rapidly in recent months. The pandemic and the associated containment measures have weakened consumption and investment, and disrupted businesses’ operations and the supply of labor and inputs. While the global economy has begun to rebound following a gradual relaxation of lockdown measures, the continued spread of Coronavirus (COVID-19) in several parts of the world is weighing on the nascent recovery. This report focuses on the Myanmar's economic impacts of Coronavirus (COVID-19) on firms, poverty and human capital as of December 2020.